Penerapan Nilai Amanah dan Halal dalam Prosedur Penyembelihan Qurban di Lingkungan Yayasan Pertiwi Global Rawamangun : Pengabdian - Abdilah; Taryanto; Pristanto Ria Irawan; Priyoto; Latif (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Qurban is a major Islamic ritual performed annually during Eid al-Adha, carrying spiritual, social, and educational values, particularly in educational institutions. Its implementation must comply with Islamic law, upholding principles of halal, cleanliness, and trustworthiness, from animal selection to meat distribution. This community service program aims to enhance the understanding, skills, and awareness of qurban committee members and foundation residents regarding halal, safe, and sharia-compliant qurban practices. Methods include disseminating qurban jurisprudence, providing technical training on slaughtering and animal handling, and conducting participatory field simulations. Results indicate improved knowledge of Islamic law, increased awareness of trust, and enhanced technical skills among participants. The program benefits the current year’s qurban implementation and is expected to serve as an educational, professional, and sharia-compliant model for other educational institutions in the future.